Implementasi Program Eliminasi Tuberkulosis Dalam Mewujudkan Pilar Ketiga SDGS Di Kecamatan Cibeber Kabupaten Lebak - Ifdal Dikri, Muhammad Januar; Stiawati, Titi; Maisaroh, Ima (Jurnal PubBis, 2025)
The tuberculosis (TB) cases in Cibeber District are the highest compared to all other districts in Lebak Regency. This elevated number is caused by several factors, including low levels of community education, strong social stigma, and unfavorable social and economic conditions in the area. This study aims to examine the implementation of the TB Elimination Program in support of the Third Pillar of SDGs (Good Health and Well-being) in Cibeber District. The approach used is qualitative with a case study design, analyzing various factors such as policy targets, resources, implementation characteristics, attitudes of implementers, inter-organizational communication, external conditions (social, economic, and political), and the DOTS strategy. Data were collected through observations and interviews with nine categories of informants, including key informants from the Prevention and Control of Communicable Diseases (P3M) Section of the Lebak District Health Office, the Disease Surveillance and Control Division of PKM Citorek, the Health Promotion Division of PKM Citorek, the TB Officer (PJ) of PKM Citorek, representatives from the Penabulu Foundation - STPI (Stop Tuberculosis Partnership Indonesia) Lebak Banten, and health academics. Secondary informants included TB cadres from Cibeber District, community leaders, and TB patients from Cibeber District, along with literature studies and documentation. The data were analyzed using data reduction, presentation, and conclusion drawing techniques. The results indicate that the program is not yet running optimally due to low community awareness, social stigma, limited human resources and facilities, and uneven medication distribution. Although inter-organizational coordination and communication are good, community participation remains low, and unstable socio-economic conditions hinder the achievement of targets. Additionally, the DOTS strategy has not been fully effective due to limitations in diagnostic tools such as the GeneXpert (CBNAAT) and the need to improve the performance of medication supervisors (PMO). These findings highlight the importance of increasing community education, reducing social stigma, and optimizing resources and support systems to ensure the success of the TB elimination program in Cibeber District